Health risks of farmers for using and handling pesticides in the watershed “La Pila” - Jiménez Quintero, Cristian Alexander; Pantoja Estrada, Andrés Herlandi; Leonel, Hugo Ferney (Universidad y Salud, 2016)
Introduction: The village of Cabrera, in the municipality of Pasto, bases its economy on agriculture, which requires the use and handling of various chemicals that can cause health risks. Objective: To identify the main risks to which farmers are exposed for the use and improper handling of pesticides in their production work in the watershed called "La Pila" in the municipality of Pasto. Materials and Methods: The results obtained in the simulation of the dispersion of pesticides through HYSPLIT free Software and the risk assessment for immediate contact identified through established criteria in GTC45 ICONTEC were compared. Results: It was determined that the risk factor to which farmers in the area are subjected to is of chemical type; besides, the dispersion of these pollutants reaches a maximum length of dispersion of 250 m- However, despite the fact that workers are aware of the importance of the implementation of Personal Protective Equipment, they do not use them as barriers to mitigate and prevent the realization of the dangers. Conclusions: The identified risks are latent in farmers of the middle and lower area of the watershed.